Defining geosciences research data through metadata reuse - Alexandre Ribas Semeler; Luana Farias Sales; Adilson Luiz Pinto; Roberta Pereira da Silva de Paula; Valquer Cleyton Paes Gandra; Heloisa Costa (Biblios : revista electrónica de bibliotecología y ciencias de la información, 2025)
Objective. Research data refers to factual records used as primary scientific research resources. Reusing research data metadata provides a new perspective, allowing the presentation of new tests, hypotheses, and new research developments. This study aims to identify the nature of the types of Geosciences research data based on the reuse of metadata from the PANGEA Data Publisher for Earth and Environmental Science available at (https://www.pangaea.de/). The research question to be analyzed is “Can the processes of analyzing and manipulating PANGEA research data metadata be used to define a concept of Geosciences research data?” To address this question, we considered data specification attributes used by data journals to describe the nature of research data: domain of specialization, accessibility, language, data type, acquisition, source location, specific subject area, and related publications. Method. The methodology in question involved collecting, analyzing, and visualizing PANGEA research data metadata. In total, (426,272) records were downloaded from the data repository and compared to the data specifications used by data journals to describe the nature of research data in data papers. The methodology required the application of techniques and technologies used for descriptive analysis, information retrieval, data manipulation, and visualization of Dublin Core metadata. These techniques were implemented using the Python programming language and other data manipulation software, including OpenRefine and VOSviewer. Results. The results of our analysis suggest a detailed examination of the metadata for (137,218) research data records from (6) six Geosciences collections. The number of records in the Geochemistry collection is (73,992), in the Atmospheric Sciences collection it is (32,314), in the Paleontology collection it is (25,903), in the Oceanography collection it is (22,287), in the Geophysics collection it is (4,175), and in the Hydrology collection, it is (834). PANGEA's (6) six research data metadata collections allow for the discussion of a concept of Geosciences research data as a type of data on studies related to the Earth, atmosphere, and oceans, across different geo-disciplines. The data come from a range of disciplines, including geochemistry, atmospheric science, paleontology, oceanography, geophysics, and hydrology, using technologies such as satellites, electronics microscopes, climate sensors, ships, computer modeling, and others. In addition, the data are augmented by other sources related to the study of the Earth and its processes. Conclusions. In conclusion, research data metadata are domain-specific objects that serve as valuable research resources, regardless of their usage timing, purpose, data characteristics, or user. Geosciences research data combine laboratory and fieldwork techniques, utilizing technologies like satellites and climate sensors to study Earth’s processes. PANGEA metadata defines Geosciences research data as including observations, experiments, and modeling. Geosciences research data support replication, reinterpretation, and new research across disciplines, showcasing various facets of data reuse in scientific research.